The Timing of Analysts' Earnings Forecasts - Guttman, Ilan (The Accounting Review, 2010)
ABSTRACT: Existing literature assumes that the order and timing of analysts' earnings forecasts are determined exogenously. However, analysts choose when to issue their forecasts. This study develops a model that endogenizes the timing decision of analysts and analyzes their equilibrium timing strategies. In the model, analysts face a trade-off between the timeliness and the precision of their forecasts. The model introduces a timing game with two analysts, derives and analyzes its unique pure strategies equilibrium, and provides new empirical predictions about the precision and timing of analysts' forecasts. The equilibrium has one of two patterns: either the times of the analysts' forecasts cluster, or there is a separation in the times of the forecasts. The less informed and less similar the analysts are, the more likely it is that they forecast at different points in time. All else equal, analysts with a higher precision of initial private information tend to forecast earlier, and analysts with a higher learning ability tend to forecast later.